Charting The Course: Assessing Malaysia’s Preparedness for Implementing Dedicated Legal Safeguards for Older Person Care - Nur Faizira Abdul Rahman; MOHD YUSOFF, JAL ZABDI; Tahir, Zulazhar (The Malaysian Journal of Social Administration, 2025)
Based on the United Nations definition, Malaysia has become an ageing society and is estimated to be an aged society in 2030, with 15 per cent (expected 5.8 million) of its population consisting of older persons. It is essential to realise that Malaysia’s population is fast ageing, resulting in greater demand for care for older persons. The demand evidently increased during the COVID-19 pandemic. Nevertheless, can current care deliveries and services meet the demand in all care settings? What is the risk and impact of insufficient care deliveries to care components? What is the current legal protection status for older persons and care in Malaysia? In response to the questions, the authors put the premise that understanding the older person’s care current practice and safeguarding care with dedicated legal protection is a primary key and first step to be taken in order to manage needs and overcome challenges of older person care and to ensure a quality care delivery. This article aims to examine selected existing legal frameworks related to older person care and to assess Malaysia’s preparedness to implement a dedicated legal safeguard for older person care in this country. The authors further recommend a dedicated and specific statute that is not only there per se but, most notably, drafted in an enforceable clause based on best approaches for the best interest of older persons and all its care components.